Effect of Temperature on the Viability of Protoscolices of Echinococcus granulosus invitro - Atia, Amall Hassan (The Iraqi Journal of Veterinary Medicine, 2008)
A study was conducted invitro to determine the effects of storage attemperature 4 Cº upon the survival of protoscolices of Echinococcusgranulosus from 86 hydatid cysts isolated from infected donkeys . Flam cellactivity was the choice for viability , in addition using vital stain (0.1%aqueous eosin) . The result showed that higher percentage survival 94.41%in hydatid fluid for 9 days . The longest survival times of any of the samplestested was 81 days with the survival percentage 85% and the lowest was 33%for 13 days , showing movement till the end of this period . Our resultsproved the protoscolices removed from cyst retain their survival for severalweeks at refrigerator temperature when stored in hydatid fluid in test tubes .